SIMULATING THE DISTRIBUTION AND CARRYING CAPACITY OF SUSPENDED PARTICULATE MATTER (SPM) IN CAU HAI LAGOON - THUA THIEN-HUE PROVINCE BY MATHEMATICAL MODEL - An, Pham Hai; The, Nguyen Duc (Vietnam Journal of Marine Science and Technology, 2015)
By applying of regression methods to assimilate data for suspended particulate matter as the input data to mathematical model, the paper presents the results on the distribution and carrying capacity of suspended particulate matter in Cau Hai lagoon, Thua Thien-Hue province during the dry season (7/2013) and rainy season (10/2013). The initial simulation show that the water exchange in Cau Hai lagoon is weak in comparsion with that in Thuy Tu lagoon as well as Tam Giang lagoon, leading the distribution of suspended particulate matter to be dominated by seasonal and the suspended particulate matter from Truoi river. The overall mean concentration of suspended particulate matter is 30 g/m3 during dry season and 48 g/m3 in the rainy season. Notably, the carrying capacity of suspended particulate matter in Cau Hai lagoon is very low in the rainy season, with the remaining capacity of receiving being only 4%. Therefore, a small increase in the suspended particulate matter can result in the overload of suspended particulate matter in Cau Hai region.